Perceptions and acceptability of piloted Taenia solium control and elimination interventions in two endemic communities in eastern Zambia. Issue 2 (24th June 2019) - Hobbs, Emma Clare; Mwape, Kabemba Evans; Phiri, Andrew M.; Mambwe, Moses; Mambo, Richard; Thys, Séverine; Zulu, Gideon; Chembensofu, Mwelwa; Trevisan, Chiara; Van Damme, Inge; Phiri, Isaac Khozozo; Devleesschauwer, Brecht; et al.
Abstract: Infections with Taenia solium cause significant public health and economic losses worldwide. Despite effective control tools, long‐term sustained control/elimination of the parasite has not been demonstrated to date. Success of intervention programs is dependent on their acceptability to local communities. Focus group discussions (FGDs) and questionnaires (QS) were conducted in two study communities in eastern Zambia to assess local perceptions and acceptance of two piloted intervention strategies: one targeting pigs only ('control' study arm), and one integrated human‐ and pig‐based ('elimination') strategy. QS ( n  = 227) captured data regarding participation in project activities, knowledge and perceptions of T. solium and of the interventional drugs used in the study. FGDs ( n  = 18) discussed perceived advantages and disadvantages of the interventions and of the project's delivery and value. QS data revealed 67% of respondents participated in at least one educational activity, and 80% correctly identified at least one disease targeted by the education. All elimination study arm respondents ( n  = 113) had taken the human treatment, and 98% intended to do so next time. Most (70%) indicated willingness to pay for future treatments (median 0.20 USD per dose). Of pig‐owning respondents, 11/12 (92%) had allowed their pigs to be treated/vaccinated and all intended to do so again next time. Four pig owners indicated willingness to pay 0.10–0.50 USD per dose of treatment or vaccine. FGD feedback revealed positive perceptions of interventions; people reported improved health in themselves and their pigs, and fewer cysticerci in pork. Latrine use, hand washing, meat inspection and proper cooking of pork had reportedly increased since the program's inception. Preliminary assessment indicates that the piloted intervention methods are generally acceptable to the communities. The reported willingness of many respondents to pay for the medications would contribute to the feasibility of long‐term, government‐led T. solium intervention programs in future.